2018
DOI: 10.1590/s0004-2803.201800000-27
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Assessment in Patients With Rectal Cancer Treated With Curative Intent

Abstract: -Background -The treatment of median and distal rectal cancer has evolved a lot in the last decades due to the dissemination of the technique of total mesortal excision and the use of neoadjuvant chemotherapy and radiotherapy. However, this multidisciplinary approach can affect patients' quality of life in a number of ways that deserve to be adequately assessed. Objective -To evaluate immediate and late health related quality of life in patients with rectal cancer treated with curative intent. Methods -Prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…Although there was deterioration in embarrassment and body image scores in patients with stoma in studies [18], we did not observe a difference due to the very low number of patients with stoma.…”
Section: Discussioncontrasting
confidence: 74%
“…Although there was deterioration in embarrassment and body image scores in patients with stoma in studies [18], we did not observe a difference due to the very low number of patients with stoma.…”
Section: Discussioncontrasting
confidence: 74%
“…Studies in this review revealed that patients reported better body image over time 29,30,52,56,57,59,64,65 . However, patients with a stoma tended to report body image distress consistently over time and even worsening of distress 22,24,31,33,47,49,71 …”
Section: Resultsmentioning
confidence: 78%
“…The time frame for assessing body image ranged from 1 to 2 weeks after surgery 19 to 10 years 68 after completed treatment. Almost all studies assessed body image for CRC after surgery; only 7 studies measured body image before surgery 22,41,47,49,60,64,65 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations